Predicting mucosal inflammation in IBD patients using patient-reported symptom scores and a faecal calprotectin home test: protocol for a multicentre prospective validation study - Lloyd Brandts; Zlatan Mujagic; M Pierik; Tessa EH Römkens; Laura Janssen; Mariëlle Romberg-Camps; Reinier Cornelis Anthonius van Linschoten; Rachel Louise West; Lennard P L Gilissen (BMJ Open)
Introduction Crohn’s disease and ulcerative colitis are chronic inflammatory bowel diseases (IBD) with a relapsing-remitting nature. With adequate non-invasive prediction of mucosal inflammation, endoscopies can be prevented and treatment optimised earlier for better disease control. We aim to validate and recalibrate commonly used patient-reported symptom scores combined with a faecal calprotectin (FC) home test as non-invasive diagnostic tool for remote monitoring of IBD, both in daily practice and in a strict trial setting. Endoscopy will be used as the gold standard.Methods and analysis In this multicentre prospective validation study, adult IBD patients are asked to fill out questionnaires regarding disease activity (Monitor IBD At Home, mobile Health Index, Manitoba IBD Index, IBD control and patient-HBI/patient-Simple Clinical Colitis Activity Index), perform a FC home test and collect a stool sample for routine laboratory FC measurement, before the start of the bowel preparation for the ileocolonoscopy. Endoscopic disease activity will be scored according to the simplified endoscopic score for Crohn’s disease (CD) for CD patients or Ulcerative Colitis Endoscopic Index for Severity and Mayo Endoscopic Subscore for ulcerative colitis patients. The main study outcome is the diagnostic test accuracy of the various patient-reported scores to assess mucosal inflammation in combination with a FC home test.Ethics and dissemination This study is approved by the Medical Research Ethics Committee of azM/UM in Maastricht dated 03 March 2021 (METC 20–085) and is monitored by the Clinical Trial Centre Maastricht according to Good Clinical Practice guidelines. Written informed consent will be obtained from all patients. Study results will be published in international peer-reviewed medical journals.Trial registration number NCT05886322